EP435 Characteristics of cervical cancer in southwestern china and the clinical significance in young patients. (1st November 2019) - Yang, L; Zeng, X; Xi, M
Abstract : Introduction/Background: The incidence of cervical cancer in young women is rising, Several authors have reported that carcinoma of cervix had a poorer prognosis and survival rates in young patients than in elder women while others found that age has no relevance with the prognosis. The aim of this study was to analyze the clinic-pathological characteristics of cervical cancer in southwestern China and discuss the features and prognosis of young patients. Methodology: A retrospective study was performed, which consisted of 1, 543 patients diagnosed with cervical cancer and underwent treatment at West China Second University Hospital between November 2005 and December 2010. Among them, 154 young patients with surgical procedures between November 2005 and December 2008 were selected for a 5-year follow-up and prognostic analysis. Results: 312 patients (20.2%) were under 35 years old in the last 5 years. The proportion of cervical adenocarcinoma remained high in young patients (13.6%), and young women with adenocarcinoma had a higher rate of LN metastases, comparing with those with squamous cell carcinoma (42.9% vs 15.8%, P=0.004). Young patients with adenocarcinoma had shorter progression-free survival than those who had squamous cell carcinoma (P=0.024). Patients aged 35 years or younger with positive postoperative pathological risk factors had shorter progression-free survival, comparing with those with negative factors (P<0.01). Conclusion: Regarding to young patients, cervical adenocarcinoma increased the risk of LN metastases and positive postoperative pathological risk factors could apparently worsen the prognosis. Histological type and LN metastases were independent prognostic factors for young patients in southwestern China. We re-emphasize the importance of health education and regular smear screening for elder women, and more attention should be paid to young patients with adenocarcinoma or LN metastases. Disclosure: Nothing to disclose.